Discover a wealth of information and get your questions answered on IDNLearn.com. Get comprehensive and trustworthy answers to all your questions from our knowledgeable community members.

Rewrite the quadratic formula and discriminant expression for clarity and proper formatting.

[tex]\[
x = \frac{-b + \sqrt{b^2 - 4ac}}{2a}
\][/tex]

[tex]\[
b^2 - 4ac
\][/tex]


Sagot :

Certainly! Let's go through the quadratic formula and the calculation of the discriminant step-by-step.

A quadratic equation is generally expressed in the form:
[tex]\[ ax^2 + bx + c = \0 \][/tex]

The quadratic formula for solving this equation for \( x \) is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2-4ac}}{2a} \][/tex]

To use this formula, we first need to calculate the discriminant, which is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]

The discriminant helps us determine the nature of the roots of the quadratic equation:
1. If \(\Delta > 0\), the equation has two distinct real roots.
2. If \(\Delta = 0\), the equation has exactly one real root (a repeated root).
3. If \(\Delta < 0\), the equation has two complex roots.

Let's assume \( a = 1 \), \( b = 1 \), and \( c = 1 \). These are the coefficients of the quadratic equation.

Step-by-Step Solution:

1. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (1)^2 - 4 \cdot 1 \cdot 1 \][/tex]
[tex]\[ \Delta = 1 - 4 \][/tex]
[tex]\[ \Delta = -3 \][/tex]

2. Determine the type of roots based on the discriminant (\(\Delta\)):
Since \(\Delta = -3\), which is less than 0, the quadratic equation will have two complex roots.

3. Use the quadratic formula to find the roots:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]

Since \(\Delta\) is negative, we will end up with an imaginary part in our solution.

Plugging in the values, we get:
[tex]\[ x = \frac{-1 \pm \sqrt{-3}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-1 \pm i\sqrt{3}}{2} \][/tex]

4. Express the roots:
The two roots are:
[tex]\[ x_1 = \frac{-1 + i\sqrt{3}}{2} \][/tex]
[tex]\[ x_2 = \frac{-1 - i\sqrt{3}}{2} \][/tex]

So, the solutions to the quadratic equation \( x^2 + x + 1 = 0 \) are:
[tex]\[ x_1 = \frac{-1 + i\sqrt{3}}{2} \][/tex]
[tex]\[ x_2 = \frac{-1 - i\sqrt{3}}{2} \][/tex]

And the discriminant is [tex]\(\Delta = -3\)[/tex]. These are the detailed steps and the final solutions for the quadratic equation using the given coefficients.